Copper‐Catalyzed Decarbonylative Cyclization of Isatins and Trifluoroacetimidohydrazides for the Synthesis of 2‐(5‐Trifluoromethyl‐1, 2, 4‐triazol‐3‐yl)anilines. Issue 5 (28th January 2022) - Zhang, Yu; Yang, Zuguang; Chen, Zhengkai; Liu, Leifang; Wu, Xiao‐Feng
Abstract: A copper‐catalyzed intramolecular decarbonylative cyclization reaction of isatins and trifluoroacetimidohydrazides for the synthesis of 2‐(5‐trifluoromethyl‐1, 2, 4‐triazol‐3‐yl)aniline derivatives has been developed. This transformation proceeds through a cascade condensation, hydrolysis, decarboxylation, and intramolecular C−N bond formation sequence. The obtained 1, 2, 4‐triazole products bearing a free amino group can be readily converted into other useful compounds. Abstract :